ANALISIS PERAMALAN HARGA SAHAM DALAM KEPUTUSAN INVESTASI PADA PERUSAHAAN PERKEBUNAN DI PT BURSA EFEK INDONESIA - Fauziah Fauziah; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2014)
This study aims to perform the movement Projected of emiten stocks AALI, GZCO, JAVA, LSIP, SGRO, SIMP, SMAR, TBLA, and UNSP and Provides an overview to the investor in making an investment decision on the plantation company in Indonesia Stock Exchange.The data used in this study is a secondary data taken from the Indonesia Stock Exchange which consists of the go public Plantation stocks data from 20 September 2011 to 20 August 2013. The method used is the method of ARIMA with Minitab 16.The results of this study can be concluded that the movement of the stock price forecasting for plantations in Indonesia Stock Exchange is general tend to decrease. technically, it is to take the advantage of short- term momentum , buy on weakness for AALI and JAVA ascending trend, whereas for stock GZCO, LSIP, SGRO, SIMP, SMAR, TBLA, and UNSP the declining trend can take steps to sell. The decline in stock prices caused by lower demand for palm oil due to the global economic crisis.